Analysis Of Regional Financial Potential For Fiscal Independence : North Maluku Case Study - Prince Charles Heston Runtunuwu; Nurdin I Muhammad; Mohammad Kotib (Journal of International Conference Proceedings, 2022)
The objectives of this study are: (1) To find out the potential development of regional performance and financial capabilities in the era of autonomy in North Halmahera Regency, (2) To know the simultaneous influence of regional financial potential from local taxes, tax revenue sharing funds / SDA, as well as tax revenue sharing funds from provinces and other local governments on fiscal independence in the era of autonomy in North Halmahera Regency, (3) To know the partial influence of local tax potential on fiscal independence in the era of autonomy in North Halmahera Regency (4) To know the partial influence of potential funds for tax revenue sharing and non-local taxes on fiscal independence in the era of autonomy in North Halmahera Regency. (5) To determine the partial effect of potential tax revenue sharing funds from provinces and other governments on fiscal independence in the era of autonomy in North Halmahera RegencyAnd the methods used in this study are methods of fiscal independence analysis and Multiple linear regression analysis.The results showed in the calculation of ratios suggesting that (1) the performance and financial capability of the region is still very low, less maximal in effectiveness and efficiency., (2) The Fund for Tax Revenue Sharing and SDA, as well as the Tax Revenue Sharing Fund of the Province and Other Local Governments have the most contribution in its influence to the Index of Fiscal Independence of North Halmahera Regency. While local taxes contribute the least influence. Local Tax Variables, Tax Revenue Sharing Funds and SDA, and Tax Revenue Sharing Funds from Provinces and Other Local Governments simultaneously positively and significantly affect fiscal independence by 73.75%, (3) Local Tax Variables are positively correlated and have a significant effect on Fiscal Independence. (4) Variable Tax Revenue Sharing Fund and SDA are positively correlated and have a significant effect on Fiscal Independence(5) Variable tax revenue sharing funds from other provinces of Local Government funds are positively correlated and have a significan effect on independence.Â Keywords: Regional Financial Potential, Fiscal Independence, Multiple Linear Regression Analysis